Nitrogen cycling and environmental impacts in upland agricultural soils in North China： A review - JU, Xiao-tang; ZHANG, Chong (Journal of Integrative Agriculture, 2017)
The upland agricultural soils in North China are distributed north of a line between the Kunlun Mountains, the Qinling Mountains and the Huaihe River. They occur in arid, semi-arid and semi-humid regions and crop production often depends on rain-fed or irrigation to supplement rainfall. This paper summarizes the characteristics of gross nitrogen（N） transformation, the fate of N fertilizer and soil N as well as the N loss pathway, and makes suggestions for proper N management in the region. The soils of the region are characterized by strong N mineralization and nitrification, and weak immobilization and denitrification ability, which lead to the production and accumulation of nitrate in the soil profile. Large amounts of accumulated nitrate have been observed in the vadose-zone in soils due to excess N fertilization in the past three decades, and this nitrate is subject to occasional leaching which leads to groundwater nitrate contamination. Under farmer＇s conventional high N fertilization practice in the winter wheat-summer maize rotation system（N application rate was approximately 600 kg ha–1 yr–1）, crop N uptake, soil residual N, NH_3 volatilization, NO_3~– leaching, and denitrification loss accounted for around 27, 30, 23, 18 and 2% of the applied fertilizer N, respectively. NH_3 volatilization and NO_3~– leaching were the most important N loss pathways while soil residual N was an important fate of N fertilizer for replenishing soil N depletion from crop production. The upland agricultural soils in North China are a large source of N_2O and total emissions in this region make up a large proportion（approximately 54%） of Chinese cropland N_2O emissions. The “non-coupled strong ammonia oxidation” process is an important mechanism of N_2O production. Slowing down ammonia oxidation after ammonium-N fertilizer or urea application and avoiding transient high soil NH4＋ concentrations are key measures for reducing N_2O emissions in this region. Further N management should aim to minimize N losses from crop and livestock production, and increase the recycling of manure and straw back to cropland. We also recommend adoption of the 4 R（Right soure, Right rate, Right time, Right place） fertilization techniques to realize proper N fertilizer management, and improving application methods or modifying fertilizer types to reduce NH_3 volatilization, improving water management to reduce NO_3~– leaching, and controlling the strong ammonia oxidation process to abate N_2O emission. Future research should focus on the study of the trade-off effects among different N loss pathways under different N application methods or fertilizer products.